Effects of coastal saline-alkali soil on rhizosphere microbial community and crop yield of cotton at different growth stages - Feng, Guoyi; Wu, Yajie; Yang, Chuanzhen; Zhang, Qian; Wang, Shulin; Dong, Ming; Wang, Yan; Qi, Hong; Guo, Lixue (Frontiers in Microbiology, 2024)
Soil salinization is a global constraint that significantly hampers agricultural production, with cotton being an important cash crop that is not immune to its detrimental effects.The rhizosphere microbiome plays a critical role in plant health and growth, which assists plants in resisting adverse abiotic stresses including soil salinization. This study explores the impact of soil salinization on cotton, including its effects on growth, yield, soil physical and chemical properties, as well as soil bacterial community structures.The results of β-diversity analysis showed that there were significant differences in bacterial communities in saline-alkali soil at different growth stages of cotton. Besides, the more severity of soil salinization, the more abundance of Proteobacteria, Bacteroidota enriched in rhizosphere bacterial composition where the abundance of Acidobacteriota exhibited the opposite trend. And the co-occurrence network analysis showed that soil salinization affected the complexity of soil bacterial co-occurrence network. These findings provide valuable insights into the mechanisms by which soil salinization affects soil microorganisms in cotton rhizosphere soil and offer guidance for improving soil salinization using beneficial microorganisms.